Konservasi Air Dan Penanggulangan Sumber Daya Air Pada Asrama Taruna Politeknik Penerbangan Indonesia Curug - Widiarto, Hendro; Taryana; Asih, Pribadi; Suprihartini, Yayuk (Politeknik Penerbangan Indonesia Curug, 2021)
The Indonesian Aviation Polytechnic Curug is a vocational school that carries out education and training programs in providing skilled personnel to meet aviation human resources. One of the important problems experienced by training participants in following the learning process that must live in the dormitory is the problem of lack of fulfillment of water needs. In the dry season it is difficult to source water, but during the rainy season the floods and water are not absorbed by the soil. The objectives of this activity are: to provide insights to school leaders to build environmentally friendly shelters, to make people aware that water is everyone's business / responsibility, to improve management of water resources management. The method of implementing this activity is by conducting counseling and training on making absorption wells, biopore channels and water reservoirs. The results achieved from this activity are that dormitory cadets are aware of and understand the importance of water resource management, both during the dry season and the rainy season and are able to practice how to make drainage channels and water reservoirs